Clinicopathological features and individualized treatment of kidney involvement in B-cell lymphoproliferative disorder - Nie, Guangyan; Sun, Lianqin; Zhang, Chengning; Yuan, Yanggang; Mao, Huijuan; Wang, Zhen; Li, Jianyong; Duan, Suyan; Xing, Changying; Zhang, Bo (Frontiers in Immunology, 2022)
Background Due to the various clinical and pathological manifestations of kidney involvement in lymphoproliferative disorder (LPD), the whole spectrum of kidney disease in LPD is still unclear, and data on kidney prognosis is scarce. Methods We retrospectively reviewed the renal pathology profiles from January 2010 to December 2021, and 28 patients with B-cell LPD combined with intact renal biopsy data were included. Results There were 20 men and eight women aging 41 to 79 years at the time of renal biopsy (median age 62 years). According to hematological diagnosis, patients were classified into four groups: chronic lymphocytic leukemia (CLL) (group1, n=7), Waldenström macroglobulinemia/lymphoplasmacytic lymphoma (WM/LPL) (group 2, n=8; WM, n=6; LPL, n=2), Other non-Hodgkin’s lymphomas (NHL) (group3, n=7; diffuse large B-cell lymphoma (DLBCL), n=2; mucosa-associated lymphoid tissue (MALT) lymphoma, n=4; Low grade B-cell lymphoma, n=1), and monoclonal gammopathy of undetermined significance/monoclonal gammopathy of renal significance (MGUS/MGRS) (group 4, n=6). Median serum creatinine (Scr) level was 129 (range,59-956) umol/L. Eight patients (29%) were presented with acute kidney injury (AKI), and five patients (18%) required hemodialysis upon admission. Twenty-three patients (82%) presented with proteinuria (median protein excretion, 2.14 g/d), 11(39%) of whom had the nephrotic syndrome. Interstitial malignant infiltration was the most frequent renal lesion (n=6). Eight patients underwent immunohistochemistry of renal tissues, of which three patients (CLL, n=1; LPL, n=1; WM, n=1) had confirmed lymphoma infiltrates, and the infiltrating cells in the remaining five patients (CLL, n=1; MALT lymphoma, n=2; MGUS, n=2) were considered unrelated to lymphoma. The most common glomerular diseases were renal amyloidosis (n=4) and membranous nephropathy (n=4). Only 20 patients were treated, 13 of whom were treated with rituximab separately or in combination. The median follow-up time was 11 months. Of these, six had achieved hematological response, complete response in five cases. Eight had achieved renal response. At the end-of-study visit, four patients died and two progressed to end stage kidney disease (ESKD). Conclusion In conclusion, the clinicopathological spectrum of renal involvement in BLPD is diverse. Renal biopsy and immunohistochemistry are required for early diagnosis and prognostic assessment.